2018
DOI: 10.18203/2349-2902.isj20180378
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study on patients presenting with obstructive jaundice

Abstract: Background: Obstructive jaundice is frequently encountered surgical disease in the practice. This study is aimed to analyse age and sex distribution and incidence of malignant or benign causes in patients presented with obstructive jaundice. Author thoroughly documented various clinical presentations in these patients, evaluated them for stage of disease and appropriate management modality available for that particular stage.Methods: This is observational study carried out in Department of General Surgery, Ham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 14 publications
1
16
1
Order By: Relevance
“…In the present study, males are more affected (55.72%) with obstructive jaundice as compared to females with Male:Female ratio of 1 As per the age distribution of the patients in the present study, elder age groups (>65 years; and 55-65 years) were commonly affected with obstructive jaundice as compared with younger age groups with the mean age of patients was 56.68±23.34 years. The mean age of incidence of obstructive jaundice found to be 48.5 years in the study done by Shukla et al 19 In a study by Sharma et al mean age was 62.5. 18 Other studies also have reported similar age groups to be involved in obstructive jaundice.…”
Section: Discussionmentioning
confidence: 89%
“…In the present study, males are more affected (55.72%) with obstructive jaundice as compared to females with Male:Female ratio of 1 As per the age distribution of the patients in the present study, elder age groups (>65 years; and 55-65 years) were commonly affected with obstructive jaundice as compared with younger age groups with the mean age of patients was 56.68±23.34 years. The mean age of incidence of obstructive jaundice found to be 48.5 years in the study done by Shukla et al 19 In a study by Sharma et al mean age was 62.5. 18 Other studies also have reported similar age groups to be involved in obstructive jaundice.…”
Section: Discussionmentioning
confidence: 89%
“…While comparing the other studies done elsewhere, the observation in present study too implies that the overall incidence of obstructive jaundice was more in females compared to males. 7 The ratio of benign versus malignant causes of obstructive jaundice in our study is 3:2. This reflects that the benign lesions are more common in patients with surgical obstructive jaundice.…”
Section: Patient Profile and Their Clinical Presentationmentioning
confidence: 49%
“…1 Choledocholithiasis is most common benign cause of obstructive jaundice. [7][8][9] The typical complaints of obstructive jaundice in our patient population were in the form of yellowish discoloration of sclera (100%), high colored urine (100%) and alcoholic stool in 70% in all the patients. However, hepatomegaly, lump abdomen and ascites were found only in patients with malignant lesions.…”
Section: Patient Profile and Their Clinical Presentationmentioning
confidence: 99%
“…In the present study, we found 137(68.5%) obstructive jaundice patients had been suffering from benign underlying biliary diseases and 63(31.5%) had been suffering from malignant biliary diseases. Shukla et al 15 found in their study that malignancy (68%) tends to be more common than benign disease (32%) as cause of obstructive jaundice. In another study from Bangladesh 13 18 , the overall incidence of post-ERCP pancreatitis is estimated to be 3% to 10% in systematic reviews 19 .…”
Section: Dscussionmentioning
confidence: 94%